Stenographic Learning Video: Design And Analysis of Video Production Using And Without Using The Script - Riski Acibi Kuncoro; Evaliata BR Sembiring (Politeknik Negeri Batam, 2020)
The selection of the right learning media is one of the factors so that students can easily understand the material being discussed. One of them is by using video learning media. Producing a video script design becomes the basis for consideration in the video-making process. The script is the main reference or a guide in conducting video production activities. The activity of producing a video without using a script is a waste of nothing. So, research was made to produce a stenography learning video using a script and without a script. This research was made using the R&D (Research & Development) research method which will then be analyzed the comparison of the results of the two videos using qualitative analysis with a comparative model. The results obtained showed that the use of texts influences the process of learning video production compared to the results obtained. So the production of stenography learning videos using scripts is more effective than without using scripts.